BIOBRIKET DARI CAMPURAN LIMBAH KULIT BIJI METE, SEKAM DAN JERAMI SERTA BUNGKIL JARAK, SEKAM DAN JERAMI - Faleh Setia Budi; Luqman Buchori (Teknik, 2012)
The petroleum is the fuel derived from fossil which can not be renewable and the deposit in the earth is not more now. In the middle 2008, the price of petroleum achieved US$ 147/Barrel because the supply of petroleum to world market was reduced. This situation forced the appearance of the alternative energy which can replace the fossil fuel in the future. Their result of combustion has low emission so that they can be reduced the pollution and were environment friendly. Biobriquette is the one alternative energy which expected to be able to replace the kerosene and LPG. This research aims to get the exactly composition and type in manufacturing of biobriquette from cashew nut shell and jatropa shell waste. The variables choose as the independence variable was the type of waste (cashew nut shell and jatropa shell) and the compositions (40, 60, 80 and 100%). The others are the fixed variable such as the size of briquette 4 cm and the total weight/biquette 25 g. The response or parameters observed in the experiment were the color, the value of calor, the length of combustion and the color of fire. The result of experiment showed that composition of the material greatly affected the quality of briquette produced. The composition 100% owns the highest calor of combustion. The calor of Jatropa waste was higher than that of cashew nut shell.